2020
DOI: 10.1088/1741-4326/ab6810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periodic gas-puffs on drift-tearing modes in ADITYA/ADITYA-U tokamak discharges

Abstract: The effect of a periodic train of short gas-puff pulses on the rotation frequency and amplitude of drift-tearing modes has been studied in ADITYA/ADITYA-U tokamak. The short gas puffs, injecting approximately ~10 17-10 18 molecules of fuel gas (hydrogen) at one toroidal location, are found to concomitantly decrease the drift-tearing mode rotation frequency and the mode amplitude during the period of injection and then recover back to its initial values when the gas pulse is over. This leads to a periodic modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…This leads to a decrease (increase) in the preexisting rotation frequency of the DTMs. Further, gas puffing during the bias voltage pulse reduces the rotation frequency, as explained by Raj et al [13]. These observations clearly indicate that the rotation of the DTMs depends on both the diamagnetic drift and the plasma rotation, and hence can be controlled by influencing either or both of these causes.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…This leads to a decrease (increase) in the preexisting rotation frequency of the DTMs. Further, gas puffing during the bias voltage pulse reduces the rotation frequency, as explained by Raj et al [13]. These observations clearly indicate that the rotation of the DTMs depends on both the diamagnetic drift and the plasma rotation, and hence can be controlled by influencing either or both of these causes.…”
Section: Introductionsupporting
confidence: 60%
“…Since RE confinement is known to be sensitive to the magnetic fluctuation (MHD) [58,59], MHD activity during the application of periodic gas puff pulses has been analyzed in detail to investigate any correlation with REs. Although the gas puffs modify both MHD modes [13] and edge fluctuations [60] in ADITYA-U, it is found that the HXR amplitude exhibits no correlation with the MHD activity in these experiments (figure 21(a)) in contrast to the strong correlation observed between HXR and edge density fluctuations…”
Section: Re Confinement By Gas Puffsmentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore, to control this transport and to improve the confinement time we need to control the interchange instability. For this purpose, various approaches have been taken in the past, such as use of gas puffs [6,7], and biasing the plasma with the help of electrodes in the tokamak boundary region. The tokamak boundary region consists of edge and scrape-off layer (SOL) regions.…”
Section: Introductionmentioning
confidence: 99%